INKUBASI BISNIS RUMAHAN IBU-IBU PKK KELURAHAN PETERONGAN SEMARANG MELALUI PEMBERDAYAAN DAN PEMBENTUKAN KELOMPOK USAHA BERSAMA SEBAGAI PENOPANG EKONOMI KELUARGA - Malebra, Irawan; Umar Farouk; Nur Rini; Sugiyanta Sugiyanta; Sandi Supaya; Paniya Paniya; Sri Wahyuni; Sri Eka Sadriatwati; Makmun Riyanto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The partners in this community service programme are PKK women of Peterongan Village, South Semarang. The objectives of this community service programme are to form a joint business group, improve business management skills, improve skills in making snacks, and increase family income. Partners in this activity are a group of PKK Peterongan mothers who have free time at home with busy taking care of children and family. Household income is not sufficient to meet the needs, so additional income is needed. The problems in the partners are that a joint business group has not been formed, the entrepreneurial spirit still needs to be developed, the skills of managing a business, making snacks, family income still needs to be increased. From these problems, the solution agreed upon by the partners is the formation of a joint business group, development of entrepreneurial spirit, training and practice in making business plans, making snack products. The output target in this programme is the formation of a joint business group, the entrepreneurial spirit increases 100%, the skills in making business plans increase 100%, the skills in making snack products increase 100%, the family income increases 10% per capita in each family.